Development of Stereo Image Analysis for Measuring Small Deformation. (2017) - Yokoyama, Tomohiro; Matsumoto, Takashi
Abstract: Carbon Fiber Reinforced Polymer, CFRP, is a promising material for the application to bridge girders. Since it is anisotropic and brittle, it is not easy to grasp its damage and fracture processes experimentally. In such a case, image analysis is able to capture characteristic strain distributions before fracture. In previous studies, CFRP box beams were tested under 4-point bending loading, and image analysis was conducted. However, because the image analysis was limited to 2D in-plane deformations, it was not able to capture 3D deformations. This study aims at developing stereo image analysis for measuring small deformation such as out-of-plane deformation.